Crossing Segregated Models with Commutative Orthogonal Block Structure - Ferreira, Sandra S. (2020)
A mixed model has segregation when its random effects part is segregated as a sub-model.We will show that under orthogonality condition, crossing segregated Commutative Orthogonal Block Structure (COBS) gives segregated COBS.